Biotechnological Potentials Of Phycobiliproteins - RICHA; VINOD K. KANNAUJIYA; MINU KESHERI; GARVITA SINGH; RAJESHWAR P. SINHA (International Journal of Pharma and Bio Sciences, 2011)
Phycobiliproteins (PBPs) are a group of antennae-protein pigments involved in light-harvesting in cyanobacteria, rhodophytes, cryptomonads and cyanelles. The phycobiliproteins are organized in supramolecular complexes, called phycobilisomes (PBSs), which are assembled in regular arrays on the outer surface of the thylakoid membrane. They have antimicrobial, antioxidant, anti-inflammatory, neuroprotective and hepatoprotective properties. In addition, they are being extensively used as natural colorants in food and cosmetics, fluorescent neoglycoproteins, probes for single particle fluorescence imaging fluorescent applications in clinical and immunological analyses. However, a comprehensive knowledge and technological base for augmenting their commercial utilities is lacking. This review deals with the structure and biotechnological potentials of phycobiliproteins.